Positron emission tomography-computed tomography in subcutaneous panniculitis-like T-cell lymphoma - Prathyusha Bikkina; Kamala Reddy; Zakir Ali; Naveen Kumar (World Journal of Nuclear Medicine)
Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare and poorly differentiated type of cutaneous T-cell lymphoma. In this variant, the lymphoma cells infiltrate preferentially into the subcutaneous adipose tissue. It is an indolent type of non-Hodgkin's lymphoma and can be mistaken for panniculitis. Here, we describe the case of a 59-year-old female patient who presented with altered skin pigmentation with diffuse plaque-like patches in the skin around the thighs and legs. A skin biopsy revealed subcutaneous lobular panniculitis composed of lymphocytes, epithelioid histiocytes, and occasional giant cells admixed with atypical lymphoid cells, which were suggestive of cutaneous lymphoma. Immunohistochemistry showed CD3 positive, CD20 negative, CD8 positive, CD4 occasional cells positive, CD56 negative, and CD5 few cells positive, confirming the diagnosis of SPTCL. Therefore, cases with atypical and nonresolving dermatological lesions should raise a suspicion of SPTCL as diagnosis against other benign conditions.